Analisis Kesalahan Penggunaan Ejaan pada Karangan Siswa Kelas X IPA SMA Negeri 3 Kefamenanu Tahun Ajaran 2020/2021 - Maria MAgdalena Pazzi; Rince Jalla Wabang; Abdul Rahim Arman Putera Dapubeang (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe the use of spelling errors in the essays of class X science students of SMA Negeri 3 Kefamenanu. The method used in this research is a qualitative descriptive method. The data collection method used in this research is documentation technique. The method used to analyze the data is the biling method. The techniques used in data analysis are: (1) replacement technique, (2) insertion technique, and (3) transformation technique. Based on the results of data collection and discussion of the analysis of spelling errors in the essays of class X IPA students of SMA Negeri 3 Kefamenanu for the 2020/2021academic year, it can be concluded that errors in the use of spelling in essays students still have errors. Of the five spellings found in student’s essays there were two errors namely in using punctuation and writing letters. Keywords: spelling, essays.error